(3OdGFd GddEYLGRs - (3YHO GdbGgQ Hf YHO GdQMef Hf eMeO GdLQLGfj, CHh HcQ,J (B471 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf MeOkG dTGcQjf (B,(3hHYO aEfG EPG JUaMfG GdaVGjd dfYQa efGRdgG ai GdTQa hLOfG GdYde ChdGgG HPdc s
(3BNQgG (B:s
(3cdGe GdHdZG Gf SFdJ Yf CZQGVge ajgG de JSJWjY dgG JHjfG Je GdcJGH s
(3HChd GdfSNI JhbjY dYHO Gddg Hf gTGe GdCfUGQi hdeMeO Hf YHO GdQMje GdMfai GdTgjQ HGHf GdUGFZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B606s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdHdGZIs